2021
DOI: 10.1186/s12888-020-03036-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological reactions and insomnia in adults with mental health disorders during the COVID-19 outbreak

Abstract: Background The 2019 coronavirus disease (COVID-19) has disrupted millions of lives and commerce. We investigated psychological reactions and insomnia during the COVID-19 outbreak in adults with mental health disorders (MDs). Methods A self-reported psychological and sleep online survey was conducted in China between February 5th to 19th, 2020. A total of 244 adults with MDs and 1116 controls matched for age, gender and sites were included. Worsened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
0
28
0
2
Order By: Relevance
“…During the early stage, insomnia symptoms have been reported to be mainly associated with acute psychological reactions due to the rapid spread of the disease (i.e., fear of getting SARS-CoV-2 infected) and the strict implementations for controlling the COVID-19 pandemic (i.e., quarantine, social distancing, lockdown, school and factory shut-down, limited access to hospitals, and traffic restrictions) [ 14 , 15 ], as well as poor sleep hygiene [ 5 , 16 ]. During the late stage of the COVID-19 pandemic, insomnia symptoms are associated with long-term effects of the COVID-19 pandemic on economic stress [ 17 , 18 ] and mental health problems [ [19] , [20] , [21] ]. Before the COVID-19 pandemic, the prevalence of insomnia symptoms in China was 15% in the adult general population [ 22 ] and 35.9% among older adults [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the early stage, insomnia symptoms have been reported to be mainly associated with acute psychological reactions due to the rapid spread of the disease (i.e., fear of getting SARS-CoV-2 infected) and the strict implementations for controlling the COVID-19 pandemic (i.e., quarantine, social distancing, lockdown, school and factory shut-down, limited access to hospitals, and traffic restrictions) [ 14 , 15 ], as well as poor sleep hygiene [ 5 , 16 ]. During the late stage of the COVID-19 pandemic, insomnia symptoms are associated with long-term effects of the COVID-19 pandemic on economic stress [ 17 , 18 ] and mental health problems [ [19] , [20] , [21] ]. Before the COVID-19 pandemic, the prevalence of insomnia symptoms in China was 15% in the adult general population [ 22 ] and 35.9% among older adults [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for higher prevalence of insomnia symptoms among patients with mental disorders may be associated with increased vulnerability to stress among patients with mental disorders [ [48] , [49] , [50] , [51] ], resulting in relapses or deterioration of an already existing mental issue. For example, in a nationwide survey which was conducted during the acute phase of the COVID-19 pandemic, we found that adults with mental disorders had higher odds for developing COVID-19 stress, worsened anxiety, and depressive and insomnia symptoms compared to individuals without mental disorders [ 21 ]. Furthermore, nationwide travel restrictions and quarantine during the acute phase of COVID-19 pandemic resulted in suspended hospital visits, which prevented patients with mental disorders from attending regular outpatient visits for evaluations and medication prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have compared the prevalence of insomnia before and during the pandemic. Two studies have demonstrated that the prevalence of insomnia has increased by about 7% during the pandemic (Lin et al, 2021;Sun et al, 2021). However, the quality of the current evidence is low, as most studies are simple cross-sectional surveys on insomnia symptoms or retrospective studies subjected to recall bias (Morin and Carrier, 2021).…”
Section: Insomniamentioning
confidence: 99%
“…Early on, mental health experts predicted negative effects for people with mental disorders in accordance with the diathesis-stress model ( Pfefferbaum and North, 2020 , Yao et al, 2020 ), for example, because of the increase of stressors such as social isolation with a simultaneous decrease in psychiatric care. These predictions have largely been fulfilled, and negative effects on people with mental disorders, such as symptom aggravation and increased risk of a COVID-19 diagnosis, have been reported ( Fancourt et al, 2020 , Sun et al, 2021 , Taquet et al, 2020 ). However, the pandemic likely exerts heterogeneous effects.…”
Section: Introductionmentioning
confidence: 99%